Deadly combination of Vaping-lnduced lung injury and Influenza: case report - Bindu H. Akkanti; Rahat Hussain; Manish K. Patel; Jayeshkumar A. Patel; Kha Dinh; Bihong Zhao; Shaimaa Elzamly; Kevin Pelicon; Klemen Petek; Ismael A. Salas de Armas; Mehmet Akay; Biswajit Kar; et al. (BMC, 2020)
Abstract Background E-cigarette and vaping use-associated acute lung injury (EVALI) has been recently recognized as a complication in individuals who use vaping devices. Another consideration is that EVALI may have an adverse influence on the outcome of intercurrent respiratory infections. We document this deadly combination in the case of a young man who had EVALI and simultaneous 41 Influenza-A infection leading to severe Acute Respiratory Distress Syndrome (ARDS). Case presentation A 27-year-old male with a history of tobacco and vaping use was admitted to hospital after two weeks of flu-like symptoms, diarrhea and vomiting. A chest x-ray was consistent with multifocal pneumonia, and microbiological tests were positive for Influenza-A and methicillin-sensitive Staphalacoccus aureus (MSSA). Bronchoscopy provided evidence of acute inhalational injury. After admission, he acutely decompensated with severe hypoxia and hypotension; he required intubation, sedation and vasopressors. He developed sepsis with acute kidney failure, liver failure, biventricular systolic dysfunction and severe rhabdomyolysis. He was placed on veno-venous (VV) extracorporeal membrane oxygenation (ECMO) initially and later changed to Veno-Arterial (VA) ECMO. Nevertheless, the patient continued to deteriorate, and he expired two weeks after admission. Conclusion This case documents that EVALI can act as a major factor leading a respiratory infection to progress into severe ARDS with a fatal outcome.